Assessing the impact of oil rent on living standards in Nigeria: Evidence from an ARDL Model - Saheed, Zakaree; Omotunde, Lawal (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2024)
Some countries are naturally endowed with abundant natural resources, which serve as a significant source of government revenue for national development. Conversely, other countries lacking such resources rely on alternative means to generate income for their developmental efforts. The disparity in development and living standards among nations, however, cannot be attributed solely to the unequal distribution of natural resources but rather to the effectiveness and efficiency with which resource revenues are utilized. This study examines the effect of oil rents on living standards in Nigeria using the Autoregressive Distributed Lag (ARDL) model. The findings reveal a positive long-run relationship between Living Standard (LS), Oil Rent (OR), and Gross Domestic Product (GDP), while a negative relationship is observed with Oil Price (OP) and Exchange Rate (ER). However, these relationships are found to be statistically insignificant. In the short run, the results show a negative and statistically significant relationship between living standards and the variables of Oil Rent, Oil Price, GDP, and Exchange Rate. These findings highlight the complex dynamics between oil rents and living standards, particularly in the context of short-run economic fluctuations. In light of these results, the study recommends that the government prioritize making all refineries operational to meet domestic fuel demand and reduce the costs associated with fuel importation, which consumes a substantial portion of the country's earnings from oil exports. Furthermore, revenues from oil exports should be channeled into productive projects that directly improve the living standards of citizens, such as investments in infrastructure, healthcare, and education. These measures are essential for ensuring that the wealth generated from natural resources translates into sustainable development and improved quality of life for the populace.